The Influence of Social Media Influencers and E-WOM on Purchase Intention: The Mediating Role of Brand Trust - Lidwina A. Aba; Berno B. Mitang (Goliterati Management Review, 2026)
Purpose: This study examines brand trust as a mediating mechanism linking social media influencers and electronic word-of-mouth (e-WOM) to purchase intention for cosmetics products among Indonesian Gen Z consumers, addressing theoretical gaps in process-oriented digital marketing research. Method/Approach: Survey data from 75 business students at Universitas Timor were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. Direct and indirect effects were tested through bias-corrected bootstrapping procedures with 5,000 resamples following contemporary mediation analysis best practices. Findings: Influencers (β = 0.445, p < .001) and e-WOM (β = 0.460, p < .001) significantly predicted brand trust. Brand trust strongly predicted purchase intention (β = 0.550, p < .001). Direct effects of influencers and e-WOM on purchase intention were non-significant. Brand trust fully mediated both relationships (indirect effects: 0.245 and 0.253, p < .05), with 60-77% variance mediated. Limitations: Cross-sectional design limits causal inference. Small sample size (n = 75) may affect generalizability. Future research should employ longitudinal designs with larger samples (n > 200) across diverse product categories and regions. Implications: Cosmetics brands should prioritize trust-building through authentic influencer partnerships and genuine e-WOM cultivation rather than direct sales promotions. Trust-first strategies prove more effective than sales-first tactics in emerging digital markets. Contribution: First study quantifying full mediation mechanism in Indonesian Gen Z cosmetics context, extending social cognitive theory and trust-based mediation frameworks to emerging market digital marketing, demonstrating trust as prerequisite for behavioral outcomes.